Making a meal for bigfoot - Owen, Ruth, 1967- (Minneapolis, Minnesota : Bearport Publishing Company, 2022)
"What do you make when bigfoot shows up at your door with an empty stomach? A meal that's tasty for your bigfoot guest (and pretty yummy for you, too)! Mix a mint and lemonade slushy and bake some crunchy fall leaf crackers and dip. Then, serve up a big bigfoot foot pizza for your new friend. Top it all off with a delicious woodland berry cheesecake that will make your guest think of home. Don't forget to explore more about bigfoot facts and fiction so you have plenty to talk about during your mythical meal"--
Includes bibliographical references and index.
Ages 7-10
Grades 2-3
Keywords: Cooking -- Juvenile literature; Sasquatch -- Juvenile literature; Cookbooks